Interjurisdictional Competition and Intracity Fiscal Disparity across Chinese Prefectural Cities. Issue 3 (30th June 2016) - Li, Huiping; Wang, Qingfang; Zheng, Chunrong
Abstract : Fierce competition among county‐level governments has substantially increased disparities in public service provision and housing markets across urban China. The role of the changing intracity administrative structure deserves scholarly, attention in this process. Building on an interdisciplinary literature of public choice and cadre promotion theory, we propose that interjurisdictional competition enlarges the intracity fiscal disparity under China's transitional administrative and fiscal systems. Results from fixed‐effect panel data modeling confirm that cities with higher level of interjurisdictional competition are associated with higher intracity fiscal disparity. This study demonstrates how transition and decentralization of the centralized fiscal system have long‐term, intended and unintended, impacts on fiscal inequality and urban stratification. With continuous urban sprawl, jurisdictional annexation, and large‐scale urban‐to‐rural migration, our study suggests that policies attempting to equalize public service distribution within cities need to consider the administrative structure at the local and regional levels.